Colorimetric Chemosensor for Sulfide Anion Detection Based on Symmetrical Nitrovanillin Azine - Diana Lestari; Tutik Dwi Wahyuningsih; Bambang Purwono (Indonesian Journal of Chemistry, 2023)
The nitrovanillin azine (NA) has been successfully synthesized and examined as a colorimetric chemosensor for sulfide anion detection. The NA was synthesized using two steps reaction. Vanillin was reacted with concentrated nitric acid to form 5-nitrovanillin (NV) then the NV was condensed with hydrazine hydrate to produce the NA. The NA was obtained and fully elucidated by FTIR, 1H-NMR, 13C-NMR, and GC-MS spectrometer. The NA activity for anionic chemosensor was then carried out on several anions such as F⁻, Cl⁻, Br⁻, I⁻, S2⁻, CN⁻, HCO3⁻, AcO⁻, H2PO4⁻, N3⁻, NO2⁻, SCN⁻, ClO3⁻, and NO3⁻. The chemosensor tests showed NA was only selective for S2− in DMF:HEPES buffer (9:1, v/v, 10 mM, pH = 7.4) giving color change from light yellow to dark green. The LOD value was 1.43 × 10−5 M and the interaction model of NA-S2− indicated deprotonation mode between the -OH group with sulfide anion in a ratio of 1:1. The NA chemosensor can be applied for qualitatively analysis of sulfide anion using filter paper strips and quantitatively analysis of sulfide anion in tap water.